2003
DOI: 10.1097/01.brs.0000083163.03910.b1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prostaglandin E1, Melatonin, and Oxytetracycline on Lipid Peroxidation, Antioxidant Defense System, Paraoxonase (PON1) Activities, and Homocysteine Levels in an Animal Model of Spinal Cord Injury

Abstract: Melatonin and oxytetracycline are effective in preventing lipid peroxidation in spinal cord injury. Paraoxonase and homocysteine can be used in monitoring the antioxidant defense system as well as superoxide dismutase and plasma glutathione peroxidase, both in injury and medicated groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 101 publications
1
19
0
Order By: Relevance
“…1 Furthermore, the increase in MDA levels and the decrease in reduced GSH levels related to ischemia are reversed with melatonin treatment. 6 Parallel to the free radical scavenger effect of melatonin, zinc supplementation caused significant decreases in MDA levels. The damage-decreasing effect of rare-earth elements in I/R damage has been mentioned before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Furthermore, the increase in MDA levels and the decrease in reduced GSH levels related to ischemia are reversed with melatonin treatment. 6 Parallel to the free radical scavenger effect of melatonin, zinc supplementation caused significant decreases in MDA levels. The damage-decreasing effect of rare-earth elements in I/R damage has been mentioned before.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in MDA levels related to spinal cord I/R were also reported in the previous studies. 5,6 However, the use of melatonin before the application considerably suppressed the increases in MDA levels during the I/R process. Melatonin, which is the main secretion product of the pineal gland, functions as a strong free radical scavenger and as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The primary traumatic mechanical injury to the spinal cord causes the death of a number of neurons that cannot be recovered and none regenerated, but some neurons continue to die for hours after traumatic SCI. This secondary neuronal death may be caused by substances released from cells in response to the primary injury.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies have found that melatonin is a very efficient scavenger of the hydroxyl and peroxyl radicals as well as an electron donor. [1][2][3][4][5][6][7][8][9] Being lipophylic and hydrophilic, it has an extreme diffusability for scavenging in cells and every subcellular compartment. In addition, it can protect membrane lipids and protein components, nucleus and all the cells.…”
Section: Introductionmentioning
confidence: 99%